A treatise of practical surveying; which is demonstrated, from its first principles. Where-in everything that is useful and curious in that art is fully considered and explained. Particularly four new and very concise methods to determine the areas of right-lined figures arithmetically, or by calculation, as well as the geometrical ones heretofore treated of; with two other new geometrical methods much more accurate and ready than any of the former, never before made public. Also the method of tracing defaced mearings from the down (or any other) survey. Very useful to persons who have any property in land, to lawyers in controverted surveys, and to practical surveyors. The whole illustrated with copper-plates. By Robert Gibson ... (1752)
Summary goes here